PENGARUH PEMBERIAN VITAMIN C TERHADAP SUSUT BOBOT SELAMA PENGANGKUTAN SAPI DARI PROVINSI LAMPUNG KE PALEMBANG - Cahyo Wicaksono; Didik Rudiono; Kusuma Adhianto (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Weight loss due stres during transportation had become economic defect on livestock business. According to this situation, an operational research using 136 cattle were held to evaluated effect of vitamin C treatment since the capability of vitamin C to reduced stres. There are 68 heads which is oral treated using 500 mg vitamin C and 68 control,  respectively. Observation were done on May-August 2014, during cattle transportation from Karang Endah Sub district, Lampung Tengah Municipal, Lampung Province to Palembang, Sumatera Selatan Province. Transportation repeated 6 times using trucks consist of half treated, which has odd tag, and control cattle. Cattle weighing were done before and after transportation, while data analyzed using t-test. Observation showed that the weight lost difference between treated (10,15%)  and control (9,74%) is 0,41% (P<0,05). Result also showed that vitamin C could saving of Rp.647.595,00/truck/ transportation.